EFFECTIVENESS OF CAMPAIGN TOOLS IN THE 2024 LEGISLATIVE CANDIDATE GENERAL ELECTION (EAST JAVA CASE STUDY) - Bayu Aulia Priyantomo; Esa Wahyu Endarti; Kodrat Sunyoto (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to measure the level of effectiveness of the campaign equipment (APK) of legislative candidates in the 2024 general election campaign with the object of East Java province. To create a positive image to attract voters, visual campaign equipment is used, namely banners, billboards, social media and so on as regulated in the General Election Commission Regulation (PKPU). So that the campaign program of each legislative candidate is very important to evaluate the effectiveness of the campaign equipment. Data collection was carried out by purposive sampling. The researcher conducted a validity test of the questions before distributing the questionnaire. After the data was collected, the data was analyzed quantitatively using the EPIC model analysis with 12 indicators. The questionnaire has been tested for validity and reliability and scaled according to the Likert rule (1-5). Then tabulation was carried out on the respondents' answers to then be averaged and applied through the EPIC diagram. The calculation results showed that two dimensions, namely the Persuasion and Communication dimensions, got a value of 3.22 and 3.14 in the effective criteria and the next two variables, namely Empathy and Impact, got a value of 3.48 and 3.47 in the effective criteria. Of the various indicators, the question with the lowest value was about the legislative candidate's promise with a score of 3.01, considering that political promises are the most vulnerable things to prospective voters and influence the next election.